On the propagation and dissipation of Alfvén waves in coronal holes - Dwivedi B.N.; Srivastava A.K. (My University, 2025)
We underline the importance of Alfvén wave dissipation in the magnetic funnels through the viscous and resistive plasma. Our results show that Alfvén waves are one of the primary energy sources in the innermost part of coronal holes where the solar wind outflow starts. © Springer 2006.